Juvenile Hormone Membrane Signaling Enhances its Intracellular Signaling Through Phosphorylation of Met and Hsp83 - Gao, Yue; Chen, Nan; Zhang, Xiangle; Li, Emma Y.; Luo, Wei; Zhang, Jie; Zhang, Wenqiang; Li, Sheng; Wang, Jian; Liu, Suning (Frontiers in Physiology, 2022)
Juvenile hormone (JH) regulates insect development and reproduction through both intracellular and membrane signaling, and the two pathways might crosstalk with each other. Recent studies have reported that JH membrane signaling induces phosphorylation of the JH intracellular receptor Met, thus enhancing its transcriptional activity. To gain more insights into JH-induced Met phosphorylation, we here performed phosphoproteomics to identify potential phosphorylation sites of Met and its paralog Germ-cell expressed (Gce) in Drosophila Kc cells. In vitro experiments demonstrate that JH-induced phosphorylation sites in the basic helix-loop-helix (bHLH) domain, but not in the Per-Arnt-Sim-B (PAS-B) domain, are required for maximization of Met transcriptional activity. Moreover, phosphoproteomics analysis reveale that JH also induces the phosphorylation of Hsp83, a chaperone protein involved in JH-activated Met nuclear import. The JH-induced Hsp83 phosphorylation at S219 facilitates Hsp83-Met binding, thus promoting Met nuclear import and its transcription. By using proteomics, subcellular distribution, and co-immunoprecipitation approaches, we further characterized 14-3-3 proteins as negative regulators of Met nuclear import through physical interaction with Hsp83. These results show that JH membrane signaling induces phosphorylation of the key components in JH intracellular signaling, such as Met and Hsp83, and consequently facilitating JH intracellular signaling.